2017
DOI: 10.1111/cea.13055
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic helminth exposure and risk of allergic diseases: A study of two generations in Norway

Abstract: SummaryBackground: Animal and human studies indicate that definitive host helminth infec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
1
22
0
1
Order By: Relevance
“…in endemic regions . Although data about Ascaris prevalence in the Nordic countries are limited, the exposure to Ascaris can be quite high in these regions, with 29% in the Bergen ECRHS III cohort . In the light of extremely low findings of HDM and HDM mite allergens in bedroom mattress samples, identifying cross‐reactive proteins of other causes is relevant for future research into the cause of allergies and sensitization to mites.…”
Section: Discussionmentioning
confidence: 99%
“…in endemic regions . Although data about Ascaris prevalence in the Nordic countries are limited, the exposure to Ascaris can be quite high in these regions, with 29% in the Bergen ECRHS III cohort . In the light of extremely low findings of HDM and HDM mite allergens in bedroom mattress samples, identifying cross‐reactive proteins of other causes is relevant for future research into the cause of allergies and sensitization to mites.…”
Section: Discussionmentioning
confidence: 99%
“…Several parasitic molecules have been implicated in modulating the immune and allergic response of helminth-infected hosts [ 27 ]. It has been described that parasite infections can develop a strong response and high levels of IgE in allergic sufferers, i.e., asthma or tropical pulmonary eosinophilia [ 28 , 29 , 30 , 31 ]. Moreover, it seems that infections by A. lumbricoides, T. canis, T. trichiura , hookworm, and S. mansoni can cause allergic reactions in humans [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that disease activity might induce changes that are transmissible to the next generation, possibly explained by epigenetic inheritance rather than by shared environment or genetics alone [94]. Furthermore, a study by Jogi et al of helminths and allergies in two generations in Norway found that fathers' Toxocara exposure was associated with daughters' allergies, and mother's Toxocara exposure with sons' allergies [81]. The sex-specific pattern might be suggestive of epigenetic transmission.…”
Section: Evidence For Transmission Across Generations In Asthma and Amentioning
confidence: 99%
“…might be a risk factor for atopic disease. Epidemiological data suggested that this risk might be associated with paternal exposure to these parasites [81].…”
Section: Maternal Pre-conception Environment and Long Lasting Influenmentioning
confidence: 99%